Diseño de una Planeación Estratégica para minimizar impactos de factores críticos en la empresa Gralco S.A. (Grupo alimenticio del Atlántico S.A.) (2022)
However, the company Gralco S.A. (Grupoalimento del Atlántico S.A.), in its quest to remain in the market, requires implementing strategic planning of high importance, which guides them to be more competitive; giving organizations that can define the course or direction of the company. When using strategic planning, you will be able to respond to the demands of your environment, for this a deep analysis that helps you achieve continuous improvement of the internal levels of the organization through strategic planning, would make it easier for the company to have a more clear of a future